Increased Whole Grain Consumption Does Not Affect Blood Biochemistry, Body Composition, or Gut Microbiology in Healthy, Low-Habitual Whole Grain Consumers. Issue 2 (3rd December 2014) - Ampatzoglou, Antonios; Atwal, Kiranjit K; Maidens, Catherine M; Williams, Charlotte L; Ross, Alastair B; Thielecke, Frank; Jonnalagadda, Satya S; Kennedy, Orla B; Yaqoob, Parveen
Abstract: Background: Whole-grain (WG) foods have been suggested to reduce the risk of cardiovascular disease, but studies are inconsistent and effects on cardiovascular risk markers are not clear. Objective: The objective of this study was to assess the impact of increasing WG consumption to at least 80 g/d on overall dietary intake, body composition, blood pressure (BP), blood lipids, blood glucose, gastrointestinal microbiology, and gastrointestinal symptoms in healthy, middle-aged adults with habitual WG intake <24 g/d. Methods: Eligible subjects [12 men, 21 women, aged 40–65 y, body mass index (BMI): 20–35 kg/m 2 ] were identified through use of food frequency questionnaires and subsequently completed 3-day food diaries (3DFDs) to confirm habitual WG consumption. Subjects consumed diets high in WG (>80 g/d) or low in WG [<16 g/d, refined-grain (RG) diet] in a crossover study with 6-wk intervention periods separated by a 4-wk washout. Adherence was achieved by specific dietary advice and provision of a range of cereal food products. The 3DFDs, diet compliance diaries, and plasma alkylresorcinols were used to verify compliance. Results: During the WG intervention, consumption increased from 28 g/d to 168 g/d ( P < 0.001), accompanied by an increase in plasma alkylresorcinols ( P < 0.001) and total fiber intake ( P < 0.001), without any effect on energy or other macronutrients. Although there were no effects on studied variables, there were trends toward increased 24-h fecal weight ( P = 0.08) and reduction in body weight ( P = 0.10) and BMI ( P = 0.08) during the WG intervention compared with the RG period. Conclusion: A combination of dietary advice and provision of commercially available food items enabled subjects with a low-moderate habitual consumption of WG to substantially increase their WG intake, but there was little effect on blood biochemical markers, body composition, BP, fecal measurements, or gut microbiology. This trial was registered at www.controlled-trials.com as ISRCTN36521837.